A closed-loop ammonium salt system for recovery of high-purity lead tetroxide product from spent lead-acid battery paste. (20th March 2020) - Li, Mingyang; Yang, Jiakuan; Liang, Sha; Wang, Junxiong; Zhang, Peiyuan; Yu, Wenhao; Hu, Jingping; Xiao, Keke; Hou, Huijie; Liu, Bingchuan; Kumar, R. Vasant
Abstract: Hydrometallurgical process for recovery of spent lead-acid battery paste shows great advantages in reducing SO2 and lead particulates emissions than traditional pyrometallurgical process. However, the hydrometallurgical process usually has drawbacks of high consumption of chemical reagents and difficulty in removing impurities (especially Fe and Ba elements) from the recovered product. In this paper, a closed-loop ammonium salt system is proposed for spent lead-acid battery paste recovery. Both recirculation of leaching reagents and preparation of low-impurity recovered products have been realized. The spent lead paste is first leached by a mixed solution of ammonium acetate, acetic acid and hydrogen peroxide. After filtration, the separated lead acetate solution is reacted with ammonium carbonate to generate lead carbonate via precipitation process. The impurity elements are efficiently removed by pH control and complexation between acetate ions and impurity elements in the leaching and precipitation processes. The soluble SO4 2− separated from the precipitation process is removed by adding barium acetate to generate solid BaSO4 by-product. At the same time, the regenerated ammonium acetate filtrate is separated and re-used in the next-round leaching process in order to realize a closed-loop process. In the 5th round of filtrate recirculation processes, the leaching ratio of lead is maintained at levels higher than 92.7 wt%. Furthermore, high-purity lead tetroxide is prepared by calcination of lead carbonate in air at 450 °C. The contents of Fe and Ba in the final recovered lead tetroxide product are as low as 2.7 and 5.2 mg/kg, respectively. The recovered lead tetroxide product meets the specifications for use as an additive in the positive active materials for making a new lead-acid battery. This study provides a feasible technology for high-value utilization of spent lead paste. Graphical abstract: Image 1 Highlights: A novel ammonium salt system is proposed to recycle spent lead-acid battery paste. Lowest contents of Fe and Ba impurities of PbCO3 and Pb3 O4 products are obtained. NH4 Ac and HAc play a synergistic role in the leaching process of spent lead paste. The NH4 Ac filtrate could be re-circulated to reduce the dose of leaching reagent. Lead recovery ratio is kept over 92.7 wt% at 5th round of filtrate recirculation.